Correlation Between Rats Hippocampal ATP Content and Delayed Encephalopathy After Acute Carbon Monoxide Poisoning - Gao H; Chen C; Zhao X; Zhao L; Zheng X; Sun H; Bao H; Wang B (Neuropsychiatric Disease and Treatment, 2023)
Haoran Gao,1,* Chao Chen,2,* Xiujie Zhao,1 Lei Zhao,1 Xiaoming Zheng,1 Haibin Sun,1 Hua Bao,1 Baojun Wang2 1Department of Neurology, Hulunbuir People’s Hospital, Hulunbuir, 021000, People’s Republic of China; 2Department of Neurology, Center Hospital of Baotou, Baotou, 014040, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hua Bao, Department of Neurology, Hulunbuir People’s Hospital, No. 20 Shengli Street, Hailar District, Hulunbuir, 021000, People’s Republic of China, Tel +86-0470-3997068, Email baohuabh81@126.com Baojun Wang, Department of Neurology, Center Hospital of Baotou, No. 61 of Huancheng Road, Donghe District, Baotou, 014040, People’s Republic of China, Tel/Fax +86-0472-6955346, Email wangbaojunwbj96@126.comObjective: To study the correlation between the adenosine triphosphate (ATP) content in the hippocampus of rats and delayed encephalopathy after acute carbon monoxide (CO) poisoning.Methods: A total of 40 male Wistar rats weighing 180– 230g, in accordance with the random number table, were selected and divided into the delayed encephalopathy after acute carbon monoxide poisoning (DEACMP: Rats with cognitive impairment after carbon monoxide poisoning) group (n = 32) and the control group (n = 8). A DEACMP rat model was generated by inhalation of CO. The Morris water maze evaluated the ability to learn and memorize in rats. The changes in neurons in the hippocampus of the rats were observed by hematoxylin-eosin (HE) staining. Lastly, the ATP content in the hippocampus of the rats was measured by high-performance liquid chromatography (HPLC).Results: The ATP content of the experimental group was significantly higher than that of the control group in the hippocampus of the rat model, so the difference was statistically significant (P < 0.05); the intra-group comparison was made for the ATP content in the experimental group, and the difference was statistically significant as group 21d > group 14d > group 7d (P < 0.05); and no significant difference was found between group 21d and group 28d (P > 0.05).Conclusion: The changes in the ATP content in the hippocampus of the rats are correlated with the occurrence of delayed encephalopathy after acute carbon monoxide poisoning; it may take part in the pathogenesis of DEACMP. This offers some elicitation to the prevention and treatment of the disease.Keywords: carbon monoxide poisoning, delayed encephalopathy, ATP, HPLC